Factors affecting recruitment variability of capelin (Mallotus villosus) in the Northwest Atlantic - Frank, Kenneth T.; Carscadden, James E. (ICES Journal of Marine Science, 1989)
Year-class formation in beach-spawning stocks of capelin ( Mallotus villosus ) in eastern Newfoundland is strongly influenced by the frequency of large-scale wind-forcing events that regulate the timing and frequency of larval drift. Coastal wind forcing causes abrupt increases in water temperature and wave turbulence which in turn trigger larval emergence. Recent analysis of capelin age-composition data revealed that the strong year classes in the beach-spawning stocks also occurred in a discrete, offshore stock of capelin on the Southeast Shoal of the Grand Bank some 350 km from the nearest spawning beach where capelin spawn annually during June/July at water depths averaging 50 m. The hypothesis tested from the observations described in this paper is that essentially the same kinds of environmental factors, operating during the immediate post-hatching period, are responsible for strong year classes in both stocks. Field sampling conducted in 1986 revealed several patterns relevant to the evaluationof the hypothesis. In September, the length-frequency distribution of capelin larvae was at least bimodal, indicative of the production of more than one cohort. The formation of the dominant cohort coincided precisely with a storm event and sharp increases in both bottom temperature and currents in the area. This sequence of changes in the water-column structure appeared to reflect an episode of destratification due to in situ mixing. A second cohort, produced in the absence of any abrupt change in the surrounding physical environment, did not fare as well as the first as evidenced by its poor showing in a later larval survey. The areal distribution of larval capelin in 1986 was similar for all sizes and coincided with the distribution of spawning capelin, indicating that larvae hatching at different times remain in approximately the same geographic location. Capelin larvae smaller than 8 mm showed a diel vertical migration but were generally confined by the pycnocline to the upper 20 m. Larvae larger than 8 mm were ...